Co-production of biohydrogen and biomethane from food waste and paper waste via recirculated two-phase anaerobic digestion process: Bioenergy yields and metabolic distribution. (March 2019) - Qin, Yu; Li, Lu; Wu, Jing; Xiao, Benyi; Hojo, Toshimasa; Kubota, Kengo; Cheng, Jun; Li, Yu-You
Graphical abstract: Highlights: Successful co-production of bioH2 and bioCH4 was achieved by R-TPAD process. The R-TPAD process was feasible to treat OFMSW (FW + PW) with PW content ≤50%. Increasing PW favored H2 yields by enriching H2 -producing bacteria in the process. The major cellulose-degrading bacteria grew only in the mesophilic phase (2nd stage). The H2 -producers were recirculated to the 1st phase after growing in the 2nd phase. Abstract: To achieve the co-production of H2 and CH4, co-digestion of food waste (FW) and paper waste (PW) was performed on the recirculated two-phase anaerobic digestion (R-TPAD). The PW content in the feedstock increased from 0% to 20%, 40% and 50% (in total solids) with FW as the rest. The results showed that bioH2 and bioCH4 were simultaneously and stably produced in the long-term operation. With the increasing PW content, the removal efficiency of volatile solids decreased slightly from 84.9% to 78.4%; the bioH2 yields increased from 50 to 79 NL-H2 /kg-VSfed while the bioCH4 yields decreased from 426 to 329 NL-CH4 /kg-VSfed . With the fixed amount of FW, adding PW could significantly increase the total bioenergy yields. The relative abundance showed that the key H2 -producing bacteria, Caproiciproducens and Thermoanaerobacterium, increased after PW addition. The microbial distribution suggests that the H2 -producers were recirculated to the first stage after proliferating in the second stage.